NUMERICAL ANALYSIS OF FLOW OVER A WIND TURBINE AIRFOIL - Janez Bitenc; Brane Širok; Ignacijo Biluš (Journal of Energy Technology, 2024)
This work presents a comparison of flow conditions over a NACA 4421 two-dimensional airfoil with a closed trailing edge (normal airfoil shape) and a new blade shape with an open trailing edge. The numerical analysis was made using software for an approximate solution of a system of conservation law equations. The results yield a comparison of numerically obtained values of the lift coefficient, as well as diagrams of pressure coefficients and velocity vectors on the airfoil, at different angles of attack. The validity of the method of computation was confirmed with a comparison of computed lift coefficient values for the closed trailing edge profile, with experimentally acquired values from literature. It is reasonable to continue the research of flow conditions with the use of the open trailing edge airfoil.